The Role of Talent Management and Employee Engagement in MSMEs Going International - Rachmawati, Dita; Sudarmiatin, Sudarmiatin; Handayati, Puji (International Journal of Business, Law, and Education, 2025)
As micro, small, and medium enterprises (MSMEs) increasingly pursue international expansion, the role of human capital becomes a strategic determinant of success. This study examines the impact of talent management and employee engagement on the internationalization of MSMEs. Talent management practices—including recruitment, development, and retention of high-potential employees—are critical in building the capabilities required to compete in global markets. Simultaneously, high levels of employee engagement foster commitment, innovation, and adaptability, which are essential in navigating the challenges of international operations. Using qualitative and quantitative methods, this research identifies key strategies that link effective talent management and engagement practices with improved organizational performance in global contexts. The findings suggest that MSMEs investing in integrated talent and engagement strategies are better positioned to sustain growth and competitiveness beyond domestic boundaries.